Super wear-resistant WB4–B super-hard ceramic by in-situ formed lubrication film in high moisture - Guixin Hou; Wenyuan Chen; Qichun Sun; Juanjuan Chen; Jiao Chen; Hui Tan; Jun Cheng; Shengyu Zhu; Jun Yang; Weimin Liu (Journal of Advanced Ceramics)
Only a few materials demonstrate ultralow wear performance in specific fragile environments. We propose a self-adaptive wear strategy to achieve excellent wear resistance at high moisture contents through a super-hard substrate and an in situ lubrication layer. We prepare “self-adaptive” super wear-resistant WB4–B ceramic with a wear rate of 1×10−7 mm3·N−1·m−1 in dry environments, which relies on the superhardness of WB4 and B dual phases to maintain microstructural stability. The wear rate decreases further to 1×10−8 mm3·N−1·m−1, accompanied by a low friction coefficient of approximately 0.1, due to the in situ H3BO3/WO3 lubrication film in the moist environment. In addition, this excellent wear resistance performance remains stable under a high contact stress of 2.81 GPa and long friction cycles of 1×105. The excellent wear resistance of WB4–B ceramic, as well as their excellent adaptability under harsh conditions, improves component performance and reliability in environments that are often considered challenging for traditional materials.